Composting and vermicomposting of aquatic macrophytes for agronomic use (Research, Society and Development, 2022)
The environmentally suitable environment for the environment possible to reuse it in the possible way for the environmental environment, the possible to reuse it for the environmental environment possible to reuse it. The use of organic particles often depends on the initial transformation into stabilized humic substances to release chemical elements. Thus, the objective was to formulate macrocompounds and vermicomposts, such as aquatic ones, for agricultural use. In the macrophyte experiment, they were protected in cultivation as a natural compost plant and composting (macrophytic composition) and cultivation (compost in pots5 L), using corn variety DBK 390 PRO3. The experiment follows the water and naturalized design, in a 2 x 3 x 5 scheme, with 2 types of products or composition, addition of only compost (addition of worms per 3 of material) ), 3 composting times (20, 40 and 60 days) and 5 doses (20, 40, 80 and 120 t ha-1), with 4 replications and one plant per pot after thinning. Both the worm and the worm increased the soil P, MO, K+, Ca2+ and Mg2+ contents and were efficient for the initial growth of corn, which did not show differences for the emergence speed index, diameter, stem, number of leaves, fresh and dry mass of shoot and root system, length and root volume, when in soil conditioned with compost or vermicompost. These results are intended for the use of vermicomposting macrophytes and show that it is possible to use them for soil chemical conditioning.